Sentimento do investidor, preços de ativos e informação contábil - Passos, Lineker Costa (2023)
This thesis aimed to examine whether IFRS adoption moderates the relationship between investor sentiment (local and global) and asset prices in emerging markets over the period 2004-2018, under the arguments of two possible ways for emerging markets following IFRS adoption: (i) attenuation of the effects of local sentiment on asset prices, considering the improved quality of accounting information at the firm level arising from the adoption of the standard; (ii) increased propagation of the effects of global sentiment on asset prices, considering that sentiment from other markets may have propagated to emerging markets as a reflection of increased foreign capital flows and higher integration between markets arising from the IFRS adoption. Three aspects of asset pricing were considered, which were reflected in three research agendas: subsequent asset returns, the valuation measure P/E ratio, and the value relevance of accounting information. Investor sentiment was measured using Baker e Wurgler (2006) North American investor sentiment series as a proxy for global sentiment, while local sentiment was estimated for each country in the sample using Baker et al. (2012) approach, using a dummy to indicate high sentiment on these measures when they were positive over the period. The IFRS adoption was measured by dummy to indicate the pre- and post-IFRS period, considering the mandatory adoption event by the sample countries (Argentina, Brazil, Chile, Mexico, and Peru) and directing the tests according to the Diff-in-Diff (DiD) approach and with total sample. Considering the first research agenda, the results showed that, at the aggregate level, subsequent market returns are lower following IFRS adoption, signaling higher propagation of the global sentiment effects on subsequent returns. Similarly, at the firm level, subsequent returns of firm portfolios are higher following IFRS adoption, including such effect attenuating the negative impact in the pre-IFRS period, and the hypotheses that the adoption of IFRS standards increases the propagation of the effects of global sentiment on subsequent asset returns at the aggregate market level and that the adoption of IFRS standards attenuates the effects of local sentiment on subsequent asset returns at the firm level cannot be rejected. Regarding the second agenda, the evidence, at the aggregate level, did not indicate in the direction that the IFRS adoption increased the propagation of the adverse effects of global sentiment on the P/E ratio, as well as, at the firm level, also did not indicate evidence in the direction of attenuating effect of IFRS adoption on the negative effects of local sentiment on the P/E ratio, thus rejecting the hypotheses that the adoption of IFRS standards increases the propagation of the effects of global sentiment on the P/E ratio at the aggregate market level and that the adoption of IFRS standards attenuates the effects of local sentiment on the P/E ratio at the firm level. Concerning the third agenda, the findings, at the aggregate level, did not indicate the direction of increasing the propagation of the adverse effects of high global sentiment on the value relevance of accounting information following IFRS adoption by the sample countries. Similarly, at the firm level, the findings pointed to little evidence in the direction of a mitigating effect of IFRS adoption on the negative effects of local sentiment on the value relevance of accounting information, thus rejecting the hypotheses that the adoption of IFRS standards increases the propagation of the effects of global sentiment on the value relevance of accounting information at the aggregate market level and that the adoption of IFRS standards attenuates the effects of local sentiment on the value relevance of accounting information at the firm level. Additional tests found that these results, overall, are robust to different time horizons of subsequent returns, alternative measures for local and global sentiment, and different measures for P/E ratio and value relevance, suggesting that the thesis that the adoption of IFRS by emerging markets represents a mechanism that can both mitigate the effects of local sentiment and increase the propagation of the effects of global sentiment in asset prices is not rejected, emphasizing that support for the thesis was only conclusively observed in the interaction between investor sentiment components (global and local) and subsequent asset returns, suggesting that further studies are needed on the events examined in this thesis.